2023
DOI: 10.1038/s41598-023-44957-z
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence of personality-dependent plasticity in dairy calf movement behaviours derived from automated data collection

Francesca Occhiuto,
Jorge A. Vázquez-Diosdado,
Andrew J. King
et al.

Abstract: Individual consistency in behaviour, known as animal personality, and behavioural plasticity in response to environmental changes are important factors shaping individual behaviour. Correlations between them, called personality-dependent plasticity, indicate that personality can affect individual reactions to the environment. In farm animals this could impact the response to management changes or stressors but has not yet been investigated. Here we use ultra-wideband location sensors to measure personality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…One study showed that some calves can have a more active and exploratory personality than others [ 47 ]. This could play a role in how calves interact and adapt to new situations such as batching, with personality traits being suggested to be considered when forming social pairings or groups [ 48 ]. In this study, calves were fed through a teat before changing onto buckets, to allow for a smoother transition to the milk troughs used when group-housed.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that some calves can have a more active and exploratory personality than others [ 47 ]. This could play a role in how calves interact and adapt to new situations such as batching, with personality traits being suggested to be considered when forming social pairings or groups [ 48 ]. In this study, calves were fed through a teat before changing onto buckets, to allow for a smoother transition to the milk troughs used when group-housed.…”
Section: Discussionmentioning
confidence: 99%